Architecture, astronomy and sacred landscape in ancient Egypt - Magli, Giulio (Cambridge University Press, 2013)
10.1 A divine king ... 10.2 ... and his divine child; 10.3 The temples of millions of years; 10.4 The end of an era and its inheritance; Appendix; Chronology of the First Twenty Dynasties; Notes; A land for eternity; A king who looks at the stars; The lords of the horizon; A mirage from Heliopolis; Sons of the sun god; The lost pyramid; Renaissance at the winter solstice; A valley for the kings; The Horizon of the Aten; The last of the greats; References; Index.